Transverse myelitis after COVID-19 disease: a case report - I. Vienažindytė; R. Balnytė; Dž. Šleiteris; M. Ališauskienė (Neurologijos seminarai)
Currently, a significant number of post-COVID-19 disease neurological disorders still occur, and precise analysis of them could expand the knowledge of the neurological community for future pandemics. It is important to evaluate and recognize potential neurological manifestations and complications of COVID-19, as some of them can progress rapidly and require urgent treatment. We present a clinical case of transverse myelitis after a COVID-19 in a 35-year-old man who was treated at the Neurology Department of the Hospital of Lithuanian University of Health Sciences Kaunas Clinics.